Articulating the African Diaspora through Rhythm: Diatonic Patterns, Nested Looping Structures, and the Music of Steve Coleman - Stewart, Jesse (Intermédialités / Intermediality, 2010)
This essay examines cyclical rhythmic structures drawn from several musical traditions rooted in the African diaspora, focusing on “diatonic rhythms” and on what saxophonist and composer Steve Coleman coined “nested looping structures.” Such rhythmic structures can be regarded not only as retentions of African musical and cultural heritage, but also as a model to understand threads of continuity that exist between many of the disparate musics and cultures that have shared African roots, but radically altered by the passage of time, cross-cultural contact and musical hybridity. Furthermore, the author argues that diatonic rhythms and nested looping structures can provide a means of actively articulating connections between different diasporic musical traditions as evidenced by some of Steve Coleman’s musical collaborations, including his pioneering work from the mid-1990s with Metrics.